Candida albicans hyphal initiation and elongation - Lu, Yang (Trends Microbiol, 2014)
The fungus Candida albicans is a benign member of the mucosal microbiota, but can cause mucosal infections and life-threatening disseminated invasive infections in susceptible individuals. The ability to switch between yeast, pseudohyphal, and hyphal growth forms (polymorphism) is one of the most investigated virulence attributes of C. albicans. Recent studies suggest that hyphal development in C. albicans requires two temporally linked regulations for initiation and maintenance of the hyphal transcriptional program. Hyphal initiation requires a rapid but temporary disappearance of the Nrg1 transcriptional repressor of hyphal morphogenesis. Hyphal maintenance requires active sensing of the surrounding environment, leading to exclusion of Nrg1 binding to promoters of hypha-specific genes or reduced NRG1 expression. We discuss recent advances in understanding the complex transcriptional regulation of hyphal gene expression. These provide molecular mechanisms underpinning phenotypic plasticity of C. albicans polymorphism.